The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10853-020-05595-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution-based design of thermal post-treatments for EBM-built Alloy 718

Abstract: Alloy 718 samples were fabricated by electron beam melting (EBM) additive manufacturing process. The work focused on systematic investigation of response of the material to various thermal post-treatments, involving hot isostatic pressing (HIPing), solution treatment (ST) and two-step aging, to tailor post-treatment procedure for EBM-built Alloy 718. Results showed that HIPing at lowered temperature can be used for attaining desired defect closure while preserving grain size. Subjecting the material to ST, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Some studies observed that heat treatments (ageing at 650 • C for 168h [19], solution treating at 980 • C for 1h [45]) and HIP treatments [46] did not affect the formation or growth of carbides, probably because the temperatures were too low. Indeed, high homogenisation temperatures were shown to result in larger carbide size [47], which is said to be stable up to 1200 • C [48].…”
Section: Evolution Of Precipitatesmentioning
confidence: 99%
“…Some studies observed that heat treatments (ageing at 650 • C for 168h [19], solution treating at 980 • C for 1h [45]) and HIP treatments [46] did not affect the formation or growth of carbides, probably because the temperatures were too low. Indeed, high homogenisation temperatures were shown to result in larger carbide size [47], which is said to be stable up to 1200 • C [48].…”
Section: Evolution Of Precipitatesmentioning
confidence: 99%